Rootstocks for Florida Stone Fruit - Ali Sarkhosh; Mercy Olmstead; Jose Chaparro; Thomas Beckman (EDIS)
Rootstocks have been used in many tree fruit systems to provide growth advantages and/or pest and disease resistance without affecting (or sometimes improving) productivity and fruit quality. In Florida, stone fruit are grown on rootstocks that specifically provide resistance to the peach root-knot nematode, Meloidogyne floridensis (Handoo, et al., 2004; Sherman, et al., 1991). Although several root-knot nematode-resistant rootstocks are available for stone fruit grown in other locations and climates, ‘Flordaguard’ peach rootstock is currently the only rootstock recommended for stone fruit production in Florida.